Diversity management as a modern approach to human resource management in algerian hospitals: A case study - Bouglimina, Aicha; Eddin Zenina, Bachir Wali (The International tax journal, 2025)
This study aims to explore the reality of diversity as a modern approach to human resource management in Algerian hospitals. Diversity is regarded as a strategy to enhance hospital performance by leveraging differences in gender, ethnicity, culture, religion, age, experience, and other characteristics within the workforce. The study population included employees of the Algeria-Cuba Friendship Eye Hospital in the Wilaya of Ouargla. Their opinions were gathered using a structured questionnaire designed to test the study's hypotheses. The questionnaire covered the main themes of the research and was distributed to a random sample. A total of 37 valid questionnaires were used for analysis. The findings revealed the existence of various internal, external, and organizational factors influencing diversity management, as perceived by the sample.